Training manual on international environmental law - Kurukulasuriya, Lal (UNEP NairobiKE, 2006)
Explores the basic principles relating to treaty law. Discusses certain aspects of the negotiation of multilateral environmental agreements. Provides an overview of the main principles and concepts in international environmental law. Identifies important emerging principles and concepts, describes the roles they play, and provides examples to illustrate some of the ways in which they have been applied. Examines the scope of Access to information, public participation in decision making and access to justice in environmental matters.